2013
DOI: 10.1093/jac/dkt385
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate international measures for outpatient antibiotic prescribing and consumption: recommendations from a national data comparison of different measures

Abstract: The number of packages is a more appropriate measure than the number of DDDs when assessing outpatient antibiotic use over time and the impact of awareness campaigns in countries dispensing 'complete packages'. We recommended the use of different complementary measures or caution when interpreting trends based only on DDDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…In France, for example, animal exposure to antimicrobials decreased by 21.7% via the oral route and increased by 8.6% via the parenteral route between 2007 and 2012, mostly due to the reduction in medicated feed usage in livestock (Anses, ). Antimicrobial usage was also described as varying seasonally (Ferech et al., ; Elseviers et al., ), partly following influenza activity (Coenen et al., ). In addition, certain characteristics of antimicrobial products themselves are evolving over time.…”
Section: For Each Study Objective What Are the Requirements Regardinmentioning
confidence: 99%
See 1 more Smart Citation
“…In France, for example, animal exposure to antimicrobials decreased by 21.7% via the oral route and increased by 8.6% via the parenteral route between 2007 and 2012, mostly due to the reduction in medicated feed usage in livestock (Anses, ). Antimicrobial usage was also described as varying seasonally (Ferech et al., ; Elseviers et al., ), partly following influenza activity (Coenen et al., ). In addition, certain characteristics of antimicrobial products themselves are evolving over time.…”
Section: For Each Study Objective What Are the Requirements Regardinmentioning
confidence: 99%
“…An increasing variety of indicators of antimicrobial usage has become available in human and animal medicine, but none has been put forward as the most appropriate to measure antimicrobial usage. The main difficulties encountered when trying to identify suitable indicators are related to (i) the number of different antimicrobial usage indicators available in both human (Coenen et al., ; Fortin et al., ) and veterinary medicine (Chauvin et al., ), (ii) the apparent discrepancies or contradictions between the results obtained from different indicators applied to the same antimicrobial usage data (Chauvin et al., , ; Dalton et al., ; Polk et al., ; Bruyndonckx et al., ), and (iii) the diversity of interests, perceived utility and needs among the stakeholders involved in the collection of antimicrobial usage data (DeVincent and Viola, ; Benedict et al., ). Indeed, a range of study objectives can be pursued with the collection of antimicrobial usage data.…”
Section: Introductionmentioning
confidence: 99%
“…Defined Daily Doses (DDD) or number of packages prescribed per 1,000 inhabitants/day. 45 An evaluation of EAAD effectiveness in the UK for instance concluded that the campaign had only led to a minimal increase in public awareness, with no observable reduction in antibiotic use. 46 However, long-running campaigns, especially in Australia and France, have been associated with modest but consistent improvements in consumer awareness, as well as a reduction in antibiotic prescribing.. 47,24 What has proved to be particularly challenging is communicating the differences between bacterial and viral infections.…”
Section: Responsible Use and Public Awarenessmentioning
confidence: 99%
“…Interestingly, for central line-associated sepsis, the positive impact of using chlorhexidine-containing dressings to reduce sepsis rates has been demonstrated in several trials [5,6]. Owing to the analogy in pathogenesis and thus causative microorganisms of the 2 device-associated infections, we initiated a before-after trial aimed at decreasing MV infection rates by using chlorhexidine-containing dressings in each patient with EVD, after completing a pilot investigation for safety issues [7].…”
Section: Clinical Infectious Diseasesmentioning
confidence: 99%
“…The difference between DID and PID is usually explained by the fact that the entire decade of the 2000s, the content of an average reimbursed package increased, both by increase of strength and size (ie, doubling the tablets for the most popular β-lactams). Also, the daily dosages of some antibiotics increased, particularly β-lactams, while the defined daily dose did not, leading some authors to consider the number of packages as a more appropriate way to quantify outpatient antibiotic consumption as well as the impact of national awareness campaigns in countries dispensing "complete packages" [5]. Never required to attend postcertification courses in the infectious diseases field.…”
mentioning
confidence: 99%